2017
DOI: 10.1073/pnas.1620592114
|View full text |Cite
|
Sign up to set email alerts
|

Control of DEMETER DNA demethylase gene transcription in male and female gamete companion cells inArabidopsis thaliana

Abstract: The DEMETER (DME) DNA glycosylase initiates active DNA demethylation via the base-excision repair pathway and is vital for reproduction in Arabidopsis thaliana. DME-mediated DNA demethylation is preferentially targeted to small, AT-rich, and nucleosome-depleted euchromatic transposable elements, influencing expression of adjacent genes and leading to imprinting in the endosperm. In the female gametophyte, DME expression and subsequent genome-wide DNA demethylation are confined to the companion cell of the egg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 33 publications
3
61
1
Order By: Relevance
“…DME glycosylase enzyme mainly operates in the DNA regions enriched with AT and acts to remove 5-methylcytosine and nick the DNA backbone, followed by repair and replacement with cytosine. Recent data suggested that in Arabidopsis DNA demethylation mediated by DME facilitates endosperm gene imprinting and potential transgenerational epigenetic regulation of transposable element demethylation required for plant reproduction [41]. We propose that remodeled, nucleosome-depleted chromatin resulted from the combined action of DDM1 and MET3, becomes preferentially targeted to DME demethylation at the sites enriched with AT such as the promoter region and influences expression of adjacent genes.…”
Section: Discussionmentioning
confidence: 89%
“…DME glycosylase enzyme mainly operates in the DNA regions enriched with AT and acts to remove 5-methylcytosine and nick the DNA backbone, followed by repair and replacement with cytosine. Recent data suggested that in Arabidopsis DNA demethylation mediated by DME facilitates endosperm gene imprinting and potential transgenerational epigenetic regulation of transposable element demethylation required for plant reproduction [41]. We propose that remodeled, nucleosome-depleted chromatin resulted from the combined action of DDM1 and MET3, becomes preferentially targeted to DME demethylation at the sites enriched with AT such as the promoter region and influences expression of adjacent genes.…”
Section: Discussionmentioning
confidence: 89%
“…polypeptides of 1,729 (DME.1) and 1,987 (DME.2) amino--acids in length (17,29). The amino acid positions denoted in this study correspond to DME.2, the predominant isoform expressed in floral tissues (19). First, we detailed the domain structure and predicted characteristics of the catalytic and non--catalytic regions of the DME protein.…”
Section: Dme Encodes At Least Two Alternatively Spliced Variants Capmentioning
confidence: 99%
“…The A, Glycosylase, and B regions of the C--terminal half of DME are conserved among the DME/ROS1 DNA glycosylase clade, and are absolutely required for DME 5mC excision activity in vitro, comprising the minimal catalytic core for direct excision of 5mC from DNA (11,17,18). DME acts specifically in the central cell of the female gametophyte and the vegetative nucleus of pollen (17,19,20). The pollen grain contains the vegetative nucleus and two sperm cells, and the vegetative nucleus contributes to the germination and growth of the pollen tube, which delivers the to sperm cells to the female gametophyte.…”
Section: Introductionmentioning
confidence: 99%
“…The vegetative and central cells, adjacent to the sperm and egg cells, respectively, are so-called gamete companion cells. In Arabidopsis thaliana, active DNA demethylation by the DNA glycosylase DEMETER (DME) occurs specifically in gamete companion cells, whereby highly specific transcriptional regulation during gametogenesis ensures DME expression is confined to these cells (9)(10)(11). DME-mediated DNA demethylation occurs at thousands of discrete loci genome-wide, including regulatory regions for genes encoding components of the Polycomb Repressive Complex 2 (PRC2); FERTILIZATION INDEPENDENT SEED 2 (FIS2) and MEDEA (MEA) inducing their monoallelic expression, i.e.…”
Section: Introductionmentioning
confidence: 99%